Isotopic Shift of Atom-Dimer Efimov Resonances in K-Rb Mixtures: Critical Effect of Multichannel Feshbach Physics - Kato, K.; Wang, Yujun; Kobayashi, J.; Julienne, P. S.; Inouye, S. (My University, 2017)
Multichannel Efimov physics is investigated in ultracold heteronuclear admixtures of K and Rb atoms. We observe a shift in the scattering length where the first atom-dimer resonance appears in the 41K−87Rb system relative to the position of the previously observed atom-dimer resonance in the 40K−87Rb system. This shift is well explained by our calculations with a three-body model including van der Waals interactions, and, more importantly, multichannel spinor physics. With only minor differences in the atomic masses of the admixtures, the shift in the atom-dimer resonance positions can be cleanly ascribed to the isolated and overlapping Feshbach resonances in the 40K−87Rb and 41K−87Rb systems, respectively. Our study demonstrates the role of multichannel Feshbach physics in determining Efimov resonances in heteronuclear three-body systems.
Keywords: Atomic & molecular collisions; Interatomic & molecular potentials; Scattering of atoms, molecules, clusters & ions; Scattering theory